Understanding of International Doctoral Students’ Challenges: A Literature Review Study - Gao, Yan (Journal of International Students, 2021)
Studies pertaining to the challenges international doctoral students confront have been disseminated at various conferences and in journals. However, there is a need to synthesize recent research to assess and advance contemporary theories about international doctoral students. Using meta-synthesis, this article discusses the literature’s main themes and the relationship between theory and the literature findings. A new tentative framework is proposed based on the results. Implications for international doctoral students’ academic success are also discussed.